The association between stock-price interest rate sensitivity and disclosures about derivative... - Schrand, Catherine M. (The Accounting Review, 1997)
Using a sample of publicly traded savings and loan associations (S&Ls), this paper provides evidence that off-balance-sheet derivatives activities are positively associated with tower stock-price interest rate sensitivity. Similar to the results for derivatives, on-balance-sheet exposures to interest rate changes, as measured by the maturity mismatch of institutions' assets and liabilities, are also value relevant. Currently, the measures of on-balance-sheet interest rate risk and the corresponding impact of derivatives used in this study are not required annual report disclosures. Rather, these data are obtained from regulatory filings. The reporting of the impact of derivatives on the corresponding measure of on-balance- sheet risk is analogous to the concept of "at-risk" disclosures for derivatives which have been encouraged by the FASB and SEC. Therefore, the results suggest that the proposed disclosures will provide value-relevant information about interest rate risk for S&Ls.